Changes in the Thickness of Ice Cover on Water Bodies Subject to Human Pressure (Silesian Upland, Southern Poland) - Solarski, Maksymilian; Rzetala, Mariusz (Frontiers in Earth Science, 2021)
The paper discusses the reasons behind the variation in the thickness of ice on 39 anthropogenic water bodies located in the Silesian Upland (southern Poland). The studies were conducted over the course of three consecutive winter seasons. The measurements and observations were scheduled every two days during the freezing and ablation of the ice, and every four days when ice cover was present. Each time the thickness of the ice cover and the snow layer covering it were measured. The results show that the 35 water bodies studied are characterised by a similar – quasi-natural – ice regime, in which ice thickness variation depends mostly on the air temperature and the thickness of the snow layer covering the ice. The ice thickness on those water bodies does not significantly differ from that observed on lakes located in northern Poland, measuring on average from circa 4 to 21 centimetres, and with maximum thicknesses ranging from circa 14 to 40 centimetres, depending on the season. Four water bodies are characterised by different ice conditions; in their case the average and maximum ice thickness was significantly lower. In the Niezdara N water body this was caused by the inflow of warmer potamic water (quasi-natural regime), whereas in Pod Borem, Sośnicka, and Somerek it was caused by discharges of warm mine water (anthropogenic regime).